Use of Battery Carbon as Electrodes in Arc Discharge Method for Fabrication of Carbon-Modified TiO2. - Isya Fitria Andhika; Carissa Hertiningtyas; Ardian Aji; Alifia Desy; Teguh Endah Saraswati; Patiha Patiha (ALCHEMY Jurnal Penelitian Kimia, 2016)
Fabrication with carbon-modified TiO2 by arc  discharge  method  in  liquid  medium has  been  studied.  This  research  was  performed  in  two  steps  including  fabrication  and characterization.  This  fabrication  was  done  by  arcdischarge  method  with  graphite electrodes from dry cell batteries and liquid medium suspension of TiO2 in ethanol 30, 50 and  70  %.  A  strong  current  was  applied  to  electrode  as  10 -50  A  (20-40  V). Nanocomposites formed  on  the  liquid  medium  surface  were  collected  and  characterized using X-ray  diffraction (XRD),scanning  electron  microscope (SEM)  dan energy  dispersive spectroscopy (EDS) to determine crystallinity, surface morphology and the constituent elements, respectively.  XRD  data  shows  that the  most  effective  fabrication  TiO2/Karbon by  liquid medium in ethanol 50  %  indicated  from  the formation of a new peak with high intensity  of TiC on 2Ɵ= 36.02 °. SEM data shows that the morphology of each aggregated TiO2/Karbon  compared  to  the  morphology  of  TiO2. In  addition,  EDS  data  shows  the presence of the element carbon, titanium and oxygen  in the same area  indicating that the successful formation of composite material between TiO2 dan carbon.